PM2.5 REMOVAL IN BUS SHELTER IN PHITSANULOK PROVINCE BY WET SCRUBER WITH IoT SYSTEM - Wansom, Akasit; Maneechot, Pisit; Jiteurtragool, Nattagit; Vitidsant, Tharapong (Srinakharinwirot University Journal of Sciences and Technology, 2024)
This research aims to improve the air quality at bus shelters near roads to protect people from PM2.5 pollution by proposing the development of a wet scrubber that integrates IoT-based methods for measuring the quality of clean air at airflow outlets and PM2.5 removal efficiency in real time via the combination of turbulent water and a spray wet scrubber. This research was divided into two parts, indoor laboratory and outdoor bus shelter experiments, which used the exact reactor size. The investigated parameters for the indoor experiment were the liquid-to-air ratio and water level above the nozzle using the old diesel pickup truck generating PM2.5. The effects of both parameters on the average PM2.5 removal efficiency were investigated in a wet scrubber with a height of 4 m and a height of 0.85 m on one side of a square section. An increasing liquid-to-air ratio and water level above the nozzle favored increasing PM2.5 removal efficiency. In addition, it was also concluded that starting with 5.14 l/m3 of liquid-to-air and 150 mm of water above the nozzle created a final liquid-to-air ratio of 9.03 l/m3, which gave an average PM2.5 removal efficiency of 87.3%. This condition was applied for operating another wet scrubber with an IoT-based system installed outdoors at the bus shelter near the road in the center of Phitsanulok city, where the PM2.5 concentration exceeded the standard. The results showed that the wet scrubber IoT-based system has a PM2.5 removal average efficiency of more than 85% or a PM2.5 concentration after treatment below 15 µg/m3, which meets the standards of the World Health Organization and the Pollution Control Department of Thailand (below 37.5 µg/m3).